Furfural Degradation in Waste Water by Advanced Oxidation Process Using UV/H2O2 - Alsaqqar, Awatif S.; Salman, Mohammed Sadeq; Abood, Waleed. M.; Ali, Dhafer F. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
Furfural is one of the one of pollutants in refinery industrial wastewaters. In this study advanced oxidation process using UV/H2O2 was investigated for furfural degradation in synthetic wastewater. The results from the experimental work showed that the degradation of furfural decreases as its concentration increases, reaching 100% at 50mg/l furfural concentration and increasing the concentration of H2O2 from 250 to 500 mg/l increased furfural removal from 40 to 60%.The degradation of furfural reached 100% after 90 min exposure time using two UV lamps, where it reached 60% using one lamp after 240 min exposure time. The rate of furfural degradation k increased at the pH and initial concentration of furfural decreased, but different H2O2concentrations indicated no significant effects on the reaction rate. UV/H2O2 process is effective for furfural degradation in wastewater at neutral pH where the disposal of such effluents will be within the environmental limitations.